2019
DOI: 10.1177/1933719118811643
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Localization of Claudin-11 in Endometriotic Epithelial Cells Compared to Endometrial Cells

Abstract: Claudins are the major components of tight junctions and are often deregulated in human cancer, permitting escape of cancer cells along with the acquisition of invasive properties. Similarly, endometrial cells also show invasive capabilities; however, the role of tight junctions in endometriosis has only rarely been examined. In this study, we analyzed the protein expression and localization of claudin-7 and claudin-11 in human eutopic and ectopic endometrium and endometrial cell lines. We identified claudin-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 34 publications
3
26
1
Order By: Relevance
“…Up to now, only four studies were published regarding claudin expression in endometriosis with their findings summarized in Table 3 . In contrast to one study showing cycle-dependent differences of mRNA expression of claudins [ 80 ], three studies found no differences in expression of claudins-2–4 and 11 [ 83 , 84 , 85 , 86 ]. Again, no significant differences between the eutopic endometrium of women with and without endometriosis could be shown for claudins-2–4, 7, and 11 ( Table 3 ).…”
Section: The Role Of Emt In Endometriosismentioning
confidence: 69%
See 3 more Smart Citations
“…Up to now, only four studies were published regarding claudin expression in endometriosis with their findings summarized in Table 3 . In contrast to one study showing cycle-dependent differences of mRNA expression of claudins [ 80 ], three studies found no differences in expression of claudins-2–4 and 11 [ 83 , 84 , 85 , 86 ]. Again, no significant differences between the eutopic endometrium of women with and without endometriosis could be shown for claudins-2–4, 7, and 11 ( Table 3 ).…”
Section: The Role Of Emt In Endometriosismentioning
confidence: 69%
“…In contrast to claudins-2, 5, 7, and 11, which are not significantly different in the ectopic endometrium compared to eutopic endometrium [ 83 , 84 , 85 , 86 ], claudin-1 and claudin-4 are significantly different, showing a decreased protein presence in peritoneal endometriosis [ 83 ]. Furthermore, claudin-4 was found to also be different in ovarian endometriosis [ 84 , 85 ] ( Table 3 ).…”
Section: The Role Of Emt In Endometriosismentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it is also an essential part of the myelin sheath in the central nervous system, which plays a dual regulatory role in enhancing bone formation and inhibiting the occurrence of osteoclasts. Recently, CLDN11 has been reported to be down-regulated in some cancers, such as hepatocellular carcinoma, malignant melanoma, gastric cancer, or cutaneous squamous cell carcinoma 10 . Thus, CLDN11 has emerged as a hot area of cancer research.…”
Section: Introductionmentioning
confidence: 99%